Analisis Manajemen Risiko dalam Pembiayaan Murabahah pada Bank Umum Syariah - difri, fanesa ainun (Maliki Interdisciplinary Journal, 2025)
This study aims to analyze the implementation of risk management in murabahah financing in Islamic commercial banks. Murabahah, as the most dominant financing product in Islamic banking, has advantages in terms of transparency, legal certainty, and ease of implementation. However, this financing still contains risks that must be managed systematically. This study uses a descriptive qualitative approach with a literature study method, examining the theory and practice of risk management based on scientific literature. The results of the study indicate that the risk management process in murabahah financing includes four main stages: identification, assessment, anticipation, and risk monitoring. In addition, strategies such as 5C analysis (Character, Capacity, Capital, Collateral, and Condition) and a restructuring approach are used in mitigating problematic financing. Good risk management not only maintains the health of financing, but also increases efficiency, competitiveness, and customer trust in Islamic banks.